Economic crises: The impact on Australia and Canada - Frank Milne (Queen's University, Department of Economics, 2012)
The Financial Crisis accelerated a latent Fiscal Crisis that had been brewing in many Western countries. The paper outlines the causes of the Financial Crisis, and how this increased expenditure and reduced revenues for many Western governments. But these additional fiscal stresses merely advanced the day of reckoning when fiscal problems had to be faced Demographics (the Baby Boom effect) dictated that reforms would be required in taxation, health care and pensions to smooth the transition. Many governments had not prepared adequately, so that the added burden of the Financial Crisis provided a double impost on budgets. The paper compares Canada and Australia in this framework, showing that there are similarities and differences that are instructive. Both countries avoided the initial Crisis, but they may not be so fortunate in the near future.
Keywords: G01; G10; H30; H60; 330